Australian nurses' and midwives' perceptions of their workplace environment during the COVID-19 pandemic. Issue 1 (February 2023) - Whiteing, Nicola; Massey, Deb; Rafferty, Rae; Penman, Olivia; Samios, Christina; Bowen, Karen; Stephens, Alexandre; Aggar, Christina
Abstract: Background: Working as a front-line worker during a pandemic is a unique situation that requires a supportive work environment. An informed understanding of nurses' and midwives' workplace experiences during a pandemic, such as COVID-19, may enable better preparation and targeted support for future pandemics at an individual, organisational, and policy level. Aim: The aim of this study was to explore nurses' and midwives' workplace experiences during the COVID-19 pandemic response. Methods: A cross-sectional online survey consisting of open-ended questions was conducted with a convenience sample of nurses and midwives ( n = 1003) working in New South Wales Health hospital settings, in Australia. Open-ended questions were analysed using content analysis. Results: Five themes were identified; 'organisational communication', 'workplace support', 'availability of personal protective equipment', 'flexible working', and 'new ways of working' . Nurses' and midwives' workplace experiences during COVID-19 were influenced by leaders who were perceived to be adaptive, authentic, responsive, transparent, and visible. While many expressed a number of workplace challenges, including access to personal protective equipment, there was opportunity to explore, develop, and evaluate new and alternate models of care and working arrangements. Conclusion: It is important that nurses and midwives are supported and well prepared to cope during pandemics in the workplace. Organisational leadership and timely dissemination of transparent pandemic plans may support nurses' adaptive workplace experiences.